Advancements in Diagnostic Technologies for Coronary Heart Disease: A Theoretical and Comparative Review for Clinical Implementation (The Science Post, 2025)
Coronary Heart Disease (CHD) remains one of the most pervasive and fatal cardiovascular conditionsglobally. With millions of deaths attributed annually to CHD-related complications, accurate and earlydiagnosis is paramount. Over the years, a range of diagnostic technologies—ranging from traditionalelectrocardiography (ECG) to sophisticated imaging techniques like cardiac MRI—have evolved to meetclinical needs. This paper provides a theoretical overview of current and emerging CHD diagnostictechnologies, highlighting their principles, advantages, and limitations. It categorizes these technologies intonon-invasive, minimally invasive, and invasive methods and introduces a theoretical framework to assesstheir clinical applicability based on accuracy, cost, accessibility, patient safety, and integration potential.Finally, the study discusses challenges in technology adoption, proposes future directions for diagnosticinnovation, and suggests strategies for optimizing CHD diagnosis in clinical settings.